Inheriting the real estate in the light of the case law of courts of Lvov appeal in the interwar period - Koredczuk, Józef (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The trial is regarding inheriting real estates which as a rule constitute the valuable ingredient of the decreasing wealth. It had this particularly material meaning in Galicji Eastern, spreading through the area of courts belonging to Lvov appeal. On account of not codifying the civil law in the Second Republic a jurisprudence had an all the greater significance. Provisions of the Austrian civil code were applicable to a recalled succession from 1811, which decision moved to the sphere of the everyday life and in this way judicial decision of courts based on them revived them. The trial is portraying all relevant issues associated with inheriting the real estate in the light of the case law of orchards of Lvov appeal.
Keywords: Austrian Civil Code; inheriting the real estate; Galicja Eastern; judicature; law of succession; courts of Lvov appeal